Sendikasyon kredisi sözleşmelerinde kredi verenler arasındaki hukukî ilişki - Berzek, Melih İbrahim (My University, 2023)
Birden fazla kişinin sınırlı sorumluluk üstlenerek birlikte kredi verdikleri sözleşmeye sendikasyon kredisi sözleşmesi denir. Türk hukukunda sendikasyon kredilerinin kredi veren tarafında olan bankalar arasındaki ilişkinin adi ortaklık olduğu kabul edilmektedir. İşbu çalışmada kredi sendikasyonu adi ortaklığında ortakların hakları ve yükümlülükleri ve söz konusu ortaklığın özeliklerinin kredi alanla kredi ilişkisini ne şekilde etkilediği incelenmiştir.

Syndicated loan contracts are such contracts that multiple lenders lend to a single borrower in which lenders assume limited liability with regards to amounts they have committed to lend. Under Turkish law sydications formed by lending banks are accepted as partnerships. In this study, the rights and obligations of lenders/ partners in a syndicatied loan agreement partnership and how the characteristics of the said partnership affect the credit relationship with regards to the borrower are examined.
Legal relationship between members of loan syndication
Keywords: Adi Ortaklık; Contracts; Credit; Kredi; Law and legislation; Ortaklık; Partnership; Sendikasyon Partnership; Sözleşmeler; Syndication; Turkey; Türkiye; Yasa ve yasama